2004
DOI: 10.2118/04-10-05
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Acid Reaction Rates of a Deep Dolomitic Gas Reservoir

Abstract: A rotating disk instrument was used to measure acid reaction rates, reaction order, and activation energy of reservoir rock from a deep dolomitic gas reservoir in Saudi Arabia. These values are required to optimize acidizing simulations. Results of more than 50 experiments are reported in this paper. Measurements were made from room temperature to 85 ° C at rotational speeds of 100 to 1,000 r/min and acid concentrations of 0.05 to 5 M HCl (0.2 to 17 wt%). The results show how acid dissolution rates change as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…More details on this instrument and the experimental procedure were given by Taylor et al 15,20,25 Calcite disks with a diameter of 1.5 inches and a thickness of 0.65 inch were soaked in 0.1 N HCl for nearly 30 minutes then thoroughly rinsed with distilled water before mounting them in the rotating disk instrument. According to Fredd and Fogler,23 this procedure greatly improves the reproducibility of dissolution rate data with the rotating disk instrument.…”
Section: The Rotating Disk Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…More details on this instrument and the experimental procedure were given by Taylor et al 15,20,25 Calcite disks with a diameter of 1.5 inches and a thickness of 0.65 inch were soaked in 0.1 N HCl for nearly 30 minutes then thoroughly rinsed with distilled water before mounting them in the rotating disk instrument. According to Fredd and Fogler,23 this procedure greatly improves the reproducibility of dissolution rate data with the rotating disk instrument.…”
Section: The Rotating Disk Apparatusmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] The dissolution rate was calculated from the slope of the first few points in plots of calcium concentration and reaction time. The initial surface area of the disk was also used to determine the dissolution rate.…”
Section: Measurements Of Calcite Dissolution Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al measured the reaction rate between deep dolomitic gas reservoirs with hydrochloric acid at different temperatures. They also concluded that acid reactivity varies highly by rock composition [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al (14,15) examined in detail the relationship between acid reaction rates and rock mineralogy for a deep, dolomitic gas reservoir. Their results showed that mineralogy significantly affected acid reaction rate, and that clay contents as low as 1 wt% could reduce the apparent reaction rate of limestone reservoir rock by up to a factor of 25.…”
Section: Introductionmentioning
confidence: 99%